Sistem Pendukung Keputusan Pemilihan Pondok Pesantren Tahfizhul Qur’An Terbaik Di Malang Menggunakan Metode Analitycal Hierarchy Process Dan Promethee - Prasetyo, Eko Teguh; Prastiningtyas, Diah Arifah; Kartikasari, Meivi (LPPM STIKI MALANG, 2021)
Islamic boarding schools are one of the educational institutions that provide non-formal education in the Islamic religious field. Many Islamic boarding schools carry out Qur'an memorization programs (tahfizhul quran). Memorizing Qur'an is an activity that is very noble in the eyes of Allah SWT, because the Prophet Sallallaahu'alaihi Wasallam said which means